ENGLISH PRONUNCIATION OF MANDAILING, PADANG AND JAVA TRIBES - Hetty Zaharani (Journal MELT (Medium for English Language Teaching), 2019)
This study presents the existence of the English pronunciation of the students from Mandailingnese, Padangnese and Javanese. The purpose of this study are to investigate (1) the sound which students pronounce English differently , (2) which regional language that is most influential on the students’ English pronunciation,(3)the reason why the students pronounce English differently. The data are gathered from sounds pronounced by the students in the second semester of IAIN Medan. Then, the Students should fill the questionennaire form related to the subject and they try to pronounce 134 words given by researcher. The students are interviewed based on the subject’s problem. As the first result, researcher found  that students pronounced some words differently as follows: a. [v] → [f], [j], [p],  b. [z] → [s], [dʒ],  c. [f] → [g], [p].  d. [s] → [c], [z]  e. [ʃ] → [z], [s], [t], [c],     f. [n] → [n], [g] ,  g. [ð] → [t], [d], [ɪ], [de], [tɪ], [də], h. [dʒ] → [j], [g], [du],  i. [ph] → [p],  j.[w]→[u],  k. [tʃ] → [c], [k], [tj], [tu]   [ge], [ʒ], [ʒɪ],   l. [th] → [t],  m. [g] → [k],   n. [kh] → [k],  o. [θ] → [t], [d]  , p. [ʒ] → [z], [ʃ], [g], [gen], [s], [ʒɪ]. The second, researcher can declare that the Javanese accent has the most influence on English pronunciation.  The third, lack of daily pronunciation practice make students are unable to pronounce normal sounds or ordinary accent.